Darda āyegā dabe pāmva : Faiza Ahamada Faiza kī śāyarī, śaḵẖsīyata aura unake zamāne para ādhārita sampūrṇa nāṭaka - Bhāṭiyā, Śilā (Rādhākrshṇa, 1979)
Based on the life of Faiz Ahmad Faiz, b. 1911, Urdu poet.